Aplikasi Pengenalan Wajah Untuk Sistem Absensi Kelas Berbasis Raspberry Pi - Setiono, Prince R.; Sompie, Sherwin R.U.A; Najoan, Meicsy E.I (Universitas Sam Ratulangi, 2020)
Abstract - In conducting attendance systems, most campuses still do attendance on paper that can be easily manipulated by irresponsible students. Students at this time are still sending or duplicating absences depending on each lecturer who enters the current course hours. With this research, a